Caries‐preventive effectiveness of two different fluoride varnishes: A randomised clinical trial in patients with multi‐bracketed fixed orthodontic appliances. Issue 1 (10th July 2022) - Sardana, Divesh; Ekambaram, Manikandan; Yang, Yanqi; McGrath, Colman P.; Yiu, Cynthia K. Y.
Abstract: Background: Patients with multi‐bracketed fixed orthodontic appliances are at a higher risk of developing enamel demineralisation. Aim: To compare the efficacy of the quarterly application of two varnishes in preventing white spot lesions (WSLs) during multi‐bracketed fixed orthodontic treatment. Design: Ninety‐nine patients were randomly allocated into three intervention groups: Group A—standard oral hygiene instructions (OHI); Group B—5% sodium fluoride (NaF) varnish with standard OHI; and Group C—NaF plus tricalcium phosphate varnish with standard OHI. The outcome was assessed at 6‐monthly intervals using a quantitative laser fluorescence device, clinical evaluation and photographic evaluation on six maxillary anterior teeth. A logistic regression model using generalised estimating equations with the intervention group, time and their interaction was used to compare the occurrence of WSLs, whereas the independent‐samples Kruskal–Wallis test was used to compare the means of fluorescent values among different groups at p = .05. Results: Generalised estimating equations (with intervention and time as predictors) showed that only the effect of time was found to be significant ( p < .001), whereas there was no significant difference among the three intervention groups ( p = .305) using clinical assessment or photographic assessment ( p = .599). At the 18‐month follow‐up, sodium fluoride (NaF) varnish with standard OHI was shown to reduce the odds of WSLs by 55% ( p = .200), and NaF plus tricalcium phosphate varnish with standard OHI by 42% ( p = .327). Conclusion: The study failed to demonstrate that the quarterly application of both the study varnishes with OHI provided additional benefits compared with standard OHI alone in preventing WSLs, taking the effect of time of follow‐up into consideration. There were higher odds of developing WSLs with an increased duration of orthodontic treatment.